From a digital calibration certificate to a digital quality infrastructure - Engel Thomas (EPJ Web of Conferences)
Digitalizing the quality infrastructure is a very substantial objective for public and industrial stakeholders. A huge variety of quality related documents exist and need to be considered and transformed thoroughly into an appropriate digital representation. Early initiatives were started to digitalize the calibration certificate and the international system of units. GEMIMEG-II was a German lighthouse project with industry partners to verify and enhance the concept of digital calibration certificates for different industrial use-cases. Fundamental requirements of a digital quality document concern the standardisation of content regarding semantics, ontologies and the ability to proof originality and authenticity for all digital quality related documents. A versatile digital quality infrastructure benefits from a common structural concept supporting the variety of quality related documents and bears synergies for commonalities in content. The DX document schema and its underlying norms and standards can serve as a common conceptual framework to generate harmonized quality related digital documents and to exploit the data contained efficiently and unambiguously. International applicability and industrial processes require an efficient, productive and process integrable digital quality infrastructure. Functional requirements and opportunities of a harmonized approach for digital quality related documents will be discussed in depth.